Cortisol levels are related to neonatal pain exposure in children born very preterm at age 18 months in two independent cohorts - Mia A. McLean; Lisa Nakajima; Cecil M. Y. Chau; Joanne Weinberg; Anne R. Synnes; Steven P. Miller; Ruth E. Grunau (Wiley, 2023)
Abstract Exposure to pain‐related stress from frequent invasive procedures in the neonatal intensive care unit (NICU) has been associated with altered physiological stress regulation, neurodevelopment, and behavior in children born very preterm (≤32 weeks gestation). Previously, in a cohort born 2003-2006 (Cohort 1), we found that, at 18 months corrected age (CA), children born extremely low gestational age (ELGA; 24-28 weeks) and very low gestational age (VLGA; 29-32 weeks), had higher pre‐test cortisol levels and a different pattern of cortisol output across a developmental assessment involving cognitive challenge compared to children born full‐term (FT; 39-41 weeks). Also, greater neonatal pain‐related stress exposure among the preterm children was related to higher pre‐test cortisol levels. Given the adverse long‐term effects of neonatal pain in preterm infants and the ensuing rise in clinical concerns to appropriately manage pain in the NICU in recent years, we aimed to examine whether our findings from Cohort 1 would still be evident in an independent cohort (Cohort 2) born 2006-2011 and recruited from the same tertiary NICU in Vancouver, Canada. We also compared the cortisol patterns, clinical and socio‐demographic factors, and their interrelationships between the two cohorts. In Cohort 2, our findings using multi‐level modeling support and extend our earlier findings in Cohort 1, demonstrating that children born ELGA display higher pre‐test cortisol levels than FT. As well, greater cortisol output across assessment was related to more anxiety/depressive behaviors in children born VLGA. Importantly, children born ELGA were exposed to less neonatal pain/stress, mechanical ventilation, and morphine in Cohort 2 than Cohort 1. In both cohorts, however, cortisol levels and patterns were related to neonatal pain/stress and clinical factors (days on mechanical ventilation, overall morphine exposure). Despite less exposure to pain/stress and adverse clinical factors in Cohort 2 compared to Cohort 1, cortisol levels and patterns across cognitive challenge in preterm children at 18‐month CA were consistent across the two independent cohorts. These findings highlight that, despite improvements to neonatal care, children born extremely preterm continue to display altered HPA axis activity, which is associated with their poorer neurodevelopmental and behavioral outcomes.